The Deified Image of Thanatos, the God of Death, and its Iconographic Projection in the Latin World through the Eros-Thanatos - González Zymla, Herbert (Eikón / Imago, 2022)
Written sources on Thanatos in Classical Antiquity go beyond the vision that Hesiod, Homer, and the tragic poets embodied in their writings. This article analyzes the literary testimonies that are known about the shrines where Thanatos was worshiped (the necromancer oracle of the Arqueronte river and Gadeira), the prayers that were dedicated to Thanatos (the Orphic hymn) and the few cult images that are known (the Thanatos from the Museum of Athens, the Vatican Museum and the San Ildefonso Group from the Prado Museum). Latin written sources are also analyzed (Seneca, Virgilio, Lucano…) and the problem of assimilating a feminine noun, Mors, with a masculine divinity. If in Greek iconography the most consecrated image of Thanatos shows him transferring Sarpedon’s corpse with his brother, in Roman iconography the prototypical image is the Eros-Thanatos, linked to the torch by extinguishing his flame as an attribute. This article delves into some specific aspects of the macabre mentality of the Greco-Latin elites, who faced death with a heroic and deeply aristocratic spirit, quite different from the point of view supported by the Hedonists, who regarded death as the only levelling entity in society.